Reducing Computational Waste in Configuration Management Through a Lazy Loading and Delta Driven Approach - Oliveira, Caio R.; Melo, Arthur A.; Rocha, Carla; Alves, Isaque (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2026)
Cloud-scale infrastructure has made Green Computing a major concern in software engineering. Continuous provisioning and management of parallel systems impose a direct, quantifiable environmental footprint. Contemporary agentless Configuration Management (CM) frameworks are designed around idempotency and bulk-fetching optimizations. However, they exhibit latent hardware-level inefficiencies due to the broad use of eager-loading initialization strategies. This approach requires loading of modules and dependencies at initialization, regardless of execution context. As a result, there are redundant I/O operations, unnecessary system calls, and increased CPU idle-wait states. Altogether, these factors contribute to unsustainable energy consumption in continuous delivery pipelines. To overcome this limitation, this study uses the Design Science Research (DSR) methodology to design and empirically evaluate Ch-aOS. Ch-aOS is a novel CM framework that implements a lazy-evaluation architecture via dynamic import dispatch and a delta-driven inmemory approach to idempotency. Modules are loaded strictly on demand at runtime, eliminating superfluous initialization overhead. This limits resource consumption to each execution context’s operational requirements while maintaining batch collection mechanisms needed for idempotency. Experimental findings show that micro-level optimizations, such as reduced system calls and idle-wait CPU time, produce measurable macro-environmental benefits across large-scale deployments. This reduces hardware-level inefficiencies, specifically CPU idle-wait and unnecessary system calls, which are fundamental drivers of energy consumption at the node level.